Microstructure and sintering mechanism of C/Cu composites by mechanical alloying/spark plasma sintering. (September 2017) - Wang, Yong; Ran, Xu; Barber, Gary; Zou, Qian
This paper investigated the microstructure transformation behavior of copper–graphite composites prepared via mechanical alloying/ spark plasma sintering (MA-SPS). The results revealed that the composite powder existed in the forms of nano/submicron composite particles and pure nanoparticles. The composite particles were totally bonded together via the MA-SPS process and showed a dense and fine microstructure. The grain shape was different from that of the milled powder particles. The microhardness values of Cu–9.7 at.% C, Cu–18.1 at.% C, and Cu–25.3 at.% C composites were enhanced greatly compared with pure copper. The enhancement is due to the combination of the MA induced by high-energy ball milling from MA and discharge activation induced by pulsed current discharge from SPS in the MA-SPS fabrication process.